2022
DOI: 10.34190/ejkm.20.2.2393
|View full text |Cite
|
Sign up to set email alerts
|

Role of Training for Successful Use of Audit Tool Software

Abstract: This study examined the antecedent variables of using audit software tools to assist the auditor in completing tasks. Data were collected by distributing 303 questionnaires to auditors in Indonesia, while the technology acceptance model was used as the basis for constructing the required hypothesis. The returned questionnaires were tested for validity and reliability at the trial stage and after data collection. The data collected was analyzed using SmartPLS Ver.3.2.9 software, a structural equation modeling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Likewise, Al-Ansi et al (2017) found a significant link between IT education and training and perceived benefit. Kustono (2022) proved that IT education and training reduce anxiety and increase computer intellectual capital and ease of use. However, they failed to demonstrate their effect on perceived benefit.…”
Section: It Education and Trainingmentioning
confidence: 99%
“…Likewise, Al-Ansi et al (2017) found a significant link between IT education and training and perceived benefit. Kustono (2022) proved that IT education and training reduce anxiety and increase computer intellectual capital and ease of use. However, they failed to demonstrate their effect on perceived benefit.…”
Section: It Education and Trainingmentioning
confidence: 99%